2012
DOI: 10.2478/s11756-012-0086-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens of bark beetles (Curculionidae: Scolytinae) and other beetles in Bulgaria

Abstract: Abstract:The presence and diversity of beetle pathogens associated with different tree species in Bulgaria was investigated. In total, 818 specimens belonging to 22 beetle species were examined. Pathogens occurred in 9 host species. The infections were found in the gut (virus, nematodes, protozoans, microsporidia) and haemolymph (nematodes) of the infected insects. The following pathogen species: ItEPV, Beauveria bassiana, B. brongniartii, Isaria farinosa, Gregarina typographi, Gregarina spp., Chytridiopsis ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 27 publications
(35 reference statements)
1
8
0
Order By: Relevance
“…bassiana, B. caledonica, B. pseudobassiana and B. brongniartii (e.g. Landa et al 2001, Wegensteiner 2007, Draganova et al 2010, Takov et al 2012, Mudrončeková et al 2013, Wegensteiner et al 2015a, Barta et al 2018a. In the current survey, we recorded all of them except for B. brongniartii, which is a well-known parasite of coleopteran larvae living in soil (Zimmermann 2007).…”
Section: Species Spectrum Of Entomopathogenic Fungi In Bark Beetle Populationsmentioning
confidence: 56%
See 1 more Smart Citation
“…bassiana, B. caledonica, B. pseudobassiana and B. brongniartii (e.g. Landa et al 2001, Wegensteiner 2007, Draganova et al 2010, Takov et al 2012, Mudrončeková et al 2013, Wegensteiner et al 2015a, Barta et al 2018a. In the current survey, we recorded all of them except for B. brongniartii, which is a well-known parasite of coleopteran larvae living in soil (Zimmermann 2007).…”
Section: Species Spectrum Of Entomopathogenic Fungi In Bark Beetle Populationsmentioning
confidence: 56%
“…During the past two decades the occurrence of EPF in bark beetle populations has been documented in Europe in several studies (e.g. Landa et al 2001, Kreutz et al 2004, Wegensteiner 2007, Draganova et al 2010, Takov et al 2012, Mudrončeková et al 2013, Wegensteiner et al 2015a, Barta et al 2018a and Beauveria species have been reported as common pathogens.…”
Section: Species Spectrum Of Entomopathogenic Fungi In Bark Beetle Populationsmentioning
confidence: 99%
“…and a gregarine Gregarina cf. typographi commonly occur in the midgut of a number of representatives of the Scolytinae subfamily, and their infection level varies greatly among sites (Takov et al 2007;Holuša et al 2009;Takov et al 2010). Chytridiopsis typographi [(Weiser, 1954) Weiser, 1970] also occurs in many species of bark beetles (Haidler 1998;Händel et al 2001) and is apparently a non-specific pathogen in the intestine of a number of pests in coniferous stands (Wegensteiner 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Several species of hypocrealean entomopathogenic fungi can be identified from field-collected bark beetles and Beauveria species are usually predominant ones (Landa et al 2001;Kreutz et al 2004a;Wegensteiner 2007;Draganova et al 2010Draganova et al , 2017Mudrončeková et al 2013;Wegensteiner et al 2015a;Wegensteiner et al 2015b;Barta et al 2018a). For example, in Slovakia a majority (89%) of infected I. typographus adults collected in forests were killed with Beauveria and only a minor part was infected with Isaria (8%) or Lecanicillium (3%) (Barta et al 2018a) ) Petch can also be detected (Takov et al 2012;Barta et al 2018a). Pathogenicity of Isaria species against bark beetles in laboratory bioassays is significantly lower when compared with B. bassiana (e.g.…”
Section: Fungal Infectionsmentioning
confidence: 99%